Nurse-Led Hybrid Self-Management Education Using Smartphone Alerts to Improve Foot Care Behavior and Wound Healing Risk Among Patients with Diabetic Foot Ulcers: A Randomized Clinical Trial - Victor Maxwel; Michael Grabrilia; Alexa Barbates; William Jack Isla (Journal of Wound Research and Technology, 2026)
Background: Diabetic foot ulcers require sustained self-management beyond clinic visits. Poor foot care behavior, delayed recognition of infection, and inconsistent offloading adherence may increase wound healing risk and complicate nursing-led continuity of care. Aim: To evaluate whether nurse-led hybrid self-management education using smartphone alerts improves foot care behavior in patients with diabetic foot ulcers Approach: This randomized clinical trial enrolled 152 adults with active diabetic foot ulcers using consecutive recruitment at The Cootamundra Hospital. Eligible participants had diabetes, an active foot ulcer, smartphone access, and capacity for follow-up. Outcomes were measured at baseline, 4, 8, and 12 weeks using repeated-measures ANOVA Results: Participants had a mean age of 61.8 years; 64.5% were male. Overall attrition was 9.2%. Smartphone alert delivery reached 96.5%, and 85.7% of delivered alerts were acknowledged. Foot care behavior improved more in the intervention group than in the control group at 12 weeks, with a mean between-group change difference of 15.4 points (95% CI, 12.6-18.1). The group × time interaction was significant, F(3, 408) = 50.97, P < .001, partial η² = 0.273 Conclusions: Nurse-led hybrid self-management education supported by smartphone alerts was associated with greater improvement in foot care behavior among patients with diabetic foot ulcers Implication for Nursing Practice: Structured nursing education combined with smartphone reminders may support daily foot inspection, offloading adherence, infection-warning recognition, and continuity of diabetic foot ulcer care